Pervasive social computing : socially-aware pervasive systems and mobile applications /: socially-aware pervasive systems and mobile applications. (2016) - Kabir, Muhammad Ashad; (Computer scientist), Han, Jun; (Computer scientist), Colman, Alan
No abstract available